Pengembangan dan Evaluasi Formulasi dari Tablet Kunyah Nanopartikel Mebendazol - Muhammad Dzakwan; Widodo Priyanto (Jurnal Farmasi Indonesia, 2016)
Mebendazole is a benzimidazole derivative with broad spectrum anthelminthic activity and excellent tolerability. Orally it is rapidly absorbed and metabolized to sulfoxide and sulfone, which may be responsible for its anthelminthic action. This research aimed to formulate mebendazole nanoparticle chewable tablet to increase its dissolution velocity and impact saturation solubility. Mebendazole nanoparticle chewable tablets (300 mg) were prepared by direct compression. The tablets prepared by this method were evaluated by different parameters such as average weight, hardness, friability, disintegration, drug content and in vitro dissolution etc. All the parameters were found within the specifications. The study on the dissolution profile revealed that F1 had better dissolution rate while compared to F2, F3 and mebendazole microparticle, respectively. Assay values were within the limits of 90% to 110%.